2010
DOI: 10.2460/javma.236.9.983
|View full text |Cite
|
Sign up to set email alerts
|

Physical and clinicopathologic findings in foals derived by use of somatic cell nuclear transfer: 14 cases (2004–2008)

Abstract: Associated problems of calves resulting from use of NT have been reported, but there are few data on the outcome of foals resulting from adult somatic cell NT in horses. Although this population of foals had a lower perinatal mortality rate than has been reported for NT-derived calves, some NT-derived foals required aggressive supportive care. Birth of foals derived from NT should take place at a center equipped to handle critical care of neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 33 publications
2
35
0
1
Order By: Relevance
“…In equine reproduction, production of embryos using somatic cells as the source of nuclear transfer is nowadays both a research tool and a clinical service (Hinrichs, ). Although the number of cloned foals was small in 2012 (estimated at 100–200 worldwide; Hinrichs, ), Johnson, Clark‐Price, Choi, Hartman, and Hinrichs () reported that only 26% of cloned embryos resulted in the birth of a live foal.…”
Section: Breeding Of Sports‐and Companion Animals: Dogs Cats and Homentioning
confidence: 99%
“…In equine reproduction, production of embryos using somatic cells as the source of nuclear transfer is nowadays both a research tool and a clinical service (Hinrichs, ). Although the number of cloned foals was small in 2012 (estimated at 100–200 worldwide; Hinrichs, ), Johnson, Clark‐Price, Choi, Hartman, and Hinrichs () reported that only 26% of cloned embryos resulted in the birth of a live foal.…”
Section: Breeding Of Sports‐and Companion Animals: Dogs Cats and Homentioning
confidence: 99%
“…Only the groups led by Katrin Hinrichs in the USA (Hinrichs ; Johnson et al . ) and Cesare Galli in Italy (Galli et al . ; Lagutina et al .…”
Section: Are There Welfare‐based Reasons Which Make Animal Cloning Unmentioning
confidence: 99%
“…Hinrich's group (Johnson et al . ) reported that 26% of cloned embryos transferred by them resulted in the birth of a live foal, whereas Galli and coworkers reported that three live foals resulted from transfers of more than 100 cloned embryos (Galli et al . ; Lagutina et al .…”
Section: Are There Welfare‐based Reasons Which Make Animal Cloning Unmentioning
confidence: 99%
“…2012). Live births of cloned horse foals have been reported by several groups: eight foals by the group of Galli (C. Galli, Cremona, Italy, personal communication), fourteen foals by Texas A&M University (Johnson et al. 2010), an undisclosed number of cloned foals, stated to be ‘70+’ by ViaGen (as reported by the popular press), and at least two foals of Criollo horses in Argentina (D. Salamone, Buenos Aires, Argentina, personal communication).…”
Section: Current Strategies For Genome Resource Banking In Horsesmentioning
confidence: 99%